The Effect of Forging Process on the Fracture Toughness and Hardness of Bronze as Gamelan Instrument Material - Priambadi, IGN.; Sugita, IKG; Putri Kusuma K, CI; Nitya Santhiarsa, IGN. (Jurnal Energi Dan Manufaktur; Vol 3, No.2 Oktober 2009, 2012)
Bronze especially tin-bronze is most used as base material in making of music instrument such as bell, gamelan and others music instrument. In making of gamelan product, tin-bronze which is alloying between cooper and tin are cast, forged, harmonized and finished finally. Production process and composition are important thing should be noticed. Composition to be used by craftsman is very various depend on customary. In this research, the problem to be investigated is how much the hardness change and fracture toughness due to variation of deformation level. The purpose of this research is to know the effect of deformation level on the hardness and fracture toughness of gamelan base material, so that is hoped can yield bronze good quality as gamelan base material. At melting process of specimen, bronze is made with composition 77,5%Cu – 22,5% Sn according to craftsman composition used. The levels of specimen deformation are 5%, 10%, and 15%. Before forging process, specimens are given heat treatment with temperature 800oC during 30 minutes. Measurement of material hardness use of Vickers Method and fracture toughness test use of Three Point Bending (ASTM E 399-90) model. The result of research shows that t, the higher hardness and fracture toughness to be obtained.
Keywords: Tin -bronze, deformation level, material hardness, fracture toughness